Estrogen Receptor β as a Pharmaceutical Target. (January 2017) - Warner, Margaret; Huang, Bo; Gustafsson, Jan-Ake
Abstract : A major issue in clinical endocrinology today is how to use hormones to achieve the health benefits that they clearly can provide but avoid the negative side effects, that is, how to develop more precise medicines. This problem of how to use hormones is pervasive in clinical endocrinology. It is true for estrogen, progesterone, androgen, vitamin D, and thyroid hormone, and the problem is amplified in the case of new ligands for the more recently discovered nuclear receptors. Selective targeting of hormone receptor subtypes is one attractive way to harness the beneficial effects of hormones while reducing unwanted side effects. Here, we focus on estrogen receptor (ER)β, which has promise as a selective target in hormone replacement therapy, and in breast and prostate cancers. Trends: Targeting of nuclear receptor subtypes represents a way to differentiate between positive and negative health benefits of hormone therapy. ERα and ERβ have different distributions and functions in the body. Selective targeting of ERβ may be preferable to estrogen as hormone therapy in menopausal women. ERβ agonists may be beneficial in prostate cancer by keeping tumors to a low grade. A subset of triple-negative breast cancers is positive for ERβ, suggesting it might be a target in this difficult-to-treat disease.